Downregulation of 15‐hydroxyprostaglandin dehydrogenase by interleukin‐1β from activated macrophages leads to poor prognosis in pancreatic cancer. Issue 2 (27th January 2018) - Arima, Kota; Komohara, Yoshihiro; Bu, Luke; Tsukamoto, Masayo; Itoyama, Rumi; Miyake, Keisuke; Uchihara, Tomoyuki; Ogata, Yoko; Nakagawa, Shigeki; Okabe, Hirohisa; Imai, Katsunori; Hashimoto, Daisuke; et al.
Abstract : Chronic inflammation has a crucial role in cancer development and the progression of various tumors, including pancreatic ductal adenocarcinoma (PDAC). The arachidonate cascade is a major inflammatory pathway that produces several metabolites, such as prostaglandin E2. The enzyme 15‐hydroxyprostaglandin dehydrogenase (15‐PGDH) degrades prostaglandin and is frequently decreased in several types of cancer; however, the molecular mechanisms of 15‐PGDH suppression are unclear. The current study was carried out to elucidate the molecular mechanisms and clinical significance of 15‐PGDH suppression in PDAC. Here, we showed that interleukin‐1β (IL‐1β), a pro‐inflammatory cytokine, downregulates 15‐PGDH expression in PDAC cells, and that IL‐1β expression was inversely correlated with 15‐PGDH levels in frozen PDAC tissues. We also found that activated macrophages produced IL‐1β and reduced 15‐PGDH expression in PDAC cells. Furthermore, the number of CD163‐positive tumor‐associated macrophages was shown to be inversely correlated with 15‐PGDH levels in PDAC cells by immunohistochemical staining of 107 PDAC samples. Finally, we found that low 15‐PGDH expression was significantly associated with advanced tumors, presence of lymph node metastasis and nerve invasion, and poor prognosis in PDAC patients. Our results indicate that IL‐1β derived from TAMs suppresses 15‐PGDH expression in PDAC cells, resulting in poor prognosis of PDAC patients. Abstract : IL‐1β derived from activated macrophages down‐regulates 15‐PGDH expression in PDAC cells. Down‐regulation of 15‐PGDH promotes PDAC cell growth and leads to poor prognosis in PDAC patients.